2006
DOI: 10.1074/jbc.m606509200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic and Metabolic Studies of the Adaptations of a Prominent Adult Human Gut Symbiont, Bacteroides thetaiotaomicron, to the Suckling Period

Abstract: The adult human gut microbiota is dominated by two divisions of Bacteria, the Bacteroidetes and the Firmicutes. Assembly of this community begins at birth through processes that remain largely undefined. In this report, we examine the adaptations of Bacteroides thetaiotaomicron, a prominent member of the adult distal intestinal microbiota, during the suckling and weaning periods. Germ-free NMRI mice were colonized at birth from their gnotobiotic mothers, who harbored this anaerobic Gram-negative saccharolytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
256
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(266 citation statements)
references
References 45 publications
(56 reference statements)
8
256
0
2
Order By: Relevance
“…Also, studies with mice indicate that B. thetaiotaomicron can redirect its carbohydrate-utilizing capability from dietary to host polysaccharides according to nutrient availability (265). In another study, the adaptation of B. thetaiotomicron to utilize different nutrients during the suckling and weaning periods was investigated (27). Transcriptome analysis indicated that B. thetaiotaomicron harvested from the ceca of suckling mice has increased expression of enzymes that can utilize host-derived polysaccharides (host glycans, hexoseamines, and sialic acids that are present in mucus and the underlying gut epithelium), as well as enzymes to aid in the catabolism of mono-and oligosaccharides present in mother's milk.…”
Section: Bacteroides As Friendly Commensalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, studies with mice indicate that B. thetaiotaomicron can redirect its carbohydrate-utilizing capability from dietary to host polysaccharides according to nutrient availability (265). In another study, the adaptation of B. thetaiotomicron to utilize different nutrients during the suckling and weaning periods was investigated (27). Transcriptome analysis indicated that B. thetaiotaomicron harvested from the ceca of suckling mice has increased expression of enzymes that can utilize host-derived polysaccharides (host glycans, hexoseamines, and sialic acids that are present in mucus and the underlying gut epithelium), as well as enzymes to aid in the catabolism of mono-and oligosaccharides present in mother's milk.…”
Section: Bacteroides As Friendly Commensalsmentioning
confidence: 99%
“…Transcriptome analysis indicated that B. thetaiotaomicron harvested from the ceca of suckling mice has increased expression of enzymes that can utilize host-derived polysaccharides (host glycans, hexoseamines, and sialic acids that are present in mucus and the underlying gut epithelium), as well as enzymes to aid in the catabolism of mono-and oligosaccharides present in mother's milk. After weaning, the repertoire of sugar-digesting metabolic enzymes was expanded so that plant-derived polysaccharides (which would now be present in the gut) could be utilized (27).…”
Section: Bacteroides As Friendly Commensalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes are assembled in similarly organized, selectively regulated polysaccharide utilization loci (PULs) that encode functions necessary to detect, bind, degrade and import carbohydrate species encountered in the gut habitateither from the diet or from host glycans associated with mucus and the surfaces of epithelial cells (5)(6)(7). Studies of gnotobiotic mice colonized only with human gut-derived Bacteroides thetaiotaomicron have demonstrated that this organism can vary its pattern of expression of PULs as a function of diet, e.g., during the transition from mother's milk to a polysaccharide-rich chow consumed when mice are weaned (5), or when adult mice are switched from a diet rich in plant polysaccharides to a diet devoid of these glycans and replete with simple sugars (under the latter conditions, the organism forages on host glycans) (6,7).…”
mentioning
confidence: 99%
“…Apart from dietary components, host-derived glycans are believed to constitute a nutrient resource for (certain) members of the intestinal microbiota (3) and thus may influence the composition and activities of this complex microbial consortium. Indeed, in the absence of dietary nutrients colonization of the intestinal microorganism Bacteroides thetaiotaomicron is reliant on host-derived glycans, which it metabolizes by means of polysaccharide utilization loci (4), showing that under such circumstances endogenous carbohydrates influence the composition of the intestinal microbiota (3). Recently, another constituent of human gut microbiota, Akkermansia muciniphila, was identified as an important mucin degrader (5,6), but little is known regarding the genetic elements required for this property.…”
mentioning
confidence: 99%